Perception of Air Pollution and Annoyance Linked to Physical Levels of Pollution - Iyagba P. W; Ogundipe Nnennaya Q. (Research Parks Publishers, 2022)
The study investigates the extent of perception of air pollution and annoyance among participants in Obio/Akpor LGA. The research design adopted is correlation design. The participants were randomly selected from the populations aged 20 and above. Sample size is 123 which consist of selected participant in Obio-Akpor LGA. Annoyance due to air pollution was self-reported on a 4- point scale (1: no disturbance at all, 4: intolerable disturbance) through the following question: ‘How much are you annoyed by outdoor air pollution (from traffic, industry, etc.) if you keep the windows open?’ Perception of Air pollution is measured by a questionnaire comprising of smoking and exposure to environmental tobacco smoke (ETS), defined as regular exposure to tobacco smoke at home and/or at work. Finally, the questionnaire asked about general as well as heavy vehicle traffic intensity in front of the home. This information was collected from a four-option question, where the options were no traffic, infrequent, frequent and constant traffic. The statistical analysis was performed using Pearson product correlation at 0.05 level of significance. Annoyance was associated with estimation of individual exposure to NO2, a pollutant related to traffic. There should be adequate awareness of the risks of air pollution.